Smart City Technologies implemented in public transport in a post-COVID-19 pandemic scenario - Ferreira, Victor Garcia Figueirôa; Borchers, Tatiane; Fernandes, Ricardo Augusto Souza (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
With the global pandemic of COVID-19 completing one year, this paper intends to analyse the perceptions of public transport users about the implementation of smart city technologies. Two aspects were analysed, namely: the perception of safety regarding the use of surveillance technologies in the containment of the virus; and the perception of safety of the same technologies regarding data protection and privacy. After the identification and choice of initiatives in smart cities to be addressed, a questionnaire was prepared and made available online, in which 414 replies were considered for the final analysis, respecting the proportionality of the percentage of replies in each region to the respective population percentage. In general, technologies provide a great sense of security regarding the use of public transportation. However, they cause concern regarding data protection and privacy. From this result and with analyses in relation to the regulation of personal data, international experiences and the Brazilian reality were contrasted.